1987
DOI: 10.1055/s-2008-1052429
|View full text |Cite
|
Sign up to set email alerts
|

Ataxia-Deafness-Retardation Syndrome in Three Sisters

Abstract: Three sisters aged 16, 12 and 8 years from a consanguineous family presented with a progressive spinocerebellar ataxia combined with moderate mental retardation, progressive sensorineural hearing loss and signs of both upper and lower motor neuron disease. The patients represent the only known cases of the ataxia-deafness-retardation syndrome (McKusick #20885) except for the three brothers in the original description by Berman et al (1973). In the family described here transmission of the disease appears to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

1991
1991
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 4 publications
1
2
1
Order By: Relevance
“…The patients of Berman et al3 (three male sibs) and of Koletzko et a14 (three daughters of consanguineous parents) had clinical features very much the same as our patients, only without cataracts. However, the progressive hearing disorder and the ataxia started in infancy in the patients of both Berman et al3 and Koletzko et al 4 We feel that the syndrome in our patients does not really match one of these syndromes and, especially, the congenital cataract is only seen in our patients. Inheritance is presumably autosomal recessive.…”
Section: Discussioncontrasting
confidence: 54%
“…The patients of Berman et al3 (three male sibs) and of Koletzko et a14 (three daughters of consanguineous parents) had clinical features very much the same as our patients, only without cataracts. However, the progressive hearing disorder and the ataxia started in infancy in the patients of both Berman et al3 and Koletzko et al 4 We feel that the syndrome in our patients does not really match one of these syndromes and, especially, the congenital cataract is only seen in our patients. Inheritance is presumably autosomal recessive.…”
Section: Discussioncontrasting
confidence: 54%
“…The hearing loss associated with the present syndrome links this case with a familial syndrome with ataxia, hearing loss, and mental retardation described by several authors ( Berman et al, 1973 ; Koletzko et al, 1987 ; Begeer et al, 1991 ; Koskinen et al, 1994 ) , where hearing loss had been confirmed by audiometry‐ and/or brainstem‐evoked auditory potentials, although sural nerves have not been studied in these cases, and in HMSN‐LOM where there is hearing loss and progressive loss of nerve fibers in the sural nerve ( Kalaydjieva et al, 1996 ; Baethmann et al, 1998 ; King et al, 1999 ). The neuropathologic correlation to the hearing deficit in our patient may possibly, but cannot unequivocally, be attributed to some shrunken or hypereosinophilic neurons in the vestibulo‐cochlear nuclei, because other brainstem nuclei of cranial nerves were likewise affected.…”
Section: Discussionsupporting
confidence: 65%
“…In the majority of cases of ataxia with hypogonadism, the gonadal deficiency is secondary to decreased pituitary production of gonadotropins [Harding, 1984]. Within this group, ataxia and hypogonadism may be the only abnormalities [Volpe et al, 1963], or there may be associated features including mental retardation and deafness [Koletzko et al, 1987; Reardon et al, 1993; Richards and Rundle, 1959], and choroidal dystrophy [Limber et al, 1989]. Inheritance is autosomal recessive in most cases.…”
Section: Introductionmentioning
confidence: 99%